Prevalence of and Risk Factors for Hepatitis C Virus Infection in World Trade Center Responders - Factor, Stephanie; Desai, Vimi; Crane, Michael; Dieterich, Douglas; Boffetta, Paolo (La Medicina del Lavoro, 2023)
Background: The risk of hepatitis C virus (HCV) infection among emergency responders exposed to human remains, blood/bodily fluids, and/or sewage is unknown. Methods: A cross-sectional study of 3871 World Trade Center General Responder Cohort (WTCGRC) members followed at the Icahn School of Medicine at Mount Sinai, born from 1945-1965, and recruited from 2016-2018 were tested for HCV infection, and prevalence was compared to National Health and Nutrition Examination Survey data from 2003 to 2012. A nested case-control study compared 61 HCV antibody positive cases to 2571 controls. Multivariable logistic regression models adjusting for time of birth, traditional HCV risk factors, and type of work at the World Trade Center (WTC) site, determined if contact with human remains, blood/bodily fluids, and/or sewage at the WTC site was associated with HCV infection. Results: The age-standardized point prevalence of HCV infection among WTCGRC members was 2.98% [95% CI (2.39, 3.56)] and in the US population was 3.33% [95% CI (2.54, 4.11)] [% difference = 0.35%, 95% CI (- 0.31%, 1.01%), P=0.47]. In separate multivariable models, adjusting for possible confounders, contact with human remains was not associated with HCV infection [OR = 1.10, 95%CI(0.63, 1.91), P = 0.74)], contact with blood and/or bodily fluids was not associated with HCV infection [OR = 1.45, 95%CI(0.82, 2.56), P = 0.20], and contact with sewage was significantly associated with HCV infection [OR = 1.72, 95%CI(1.00, 2.98), P = 0.05]. Conclusion: Contact with sewage may increase the risk of HCV infection.